Rapid differential diagnosis of thyrotoxicosis using T3/T4 ratio, FT3/FT4 ratio and color doppler of thyroid gland - Rukma Rajendra Narkar (Wolters Kluwer Medknow Publications, 2021)
Context: Establishing the etiology of thyrotoxicosis is of utmost importance to plan the appropriate line of therapy. However, certain scenarios such as absence of pathognomonic clinical features of Graves' disease in some patients, or non-availability of radionuclide scanning and newer generation TRAb assays especially in resource-poor settings, necessitates utilization of other, simple and effective measures to differentiate between the two common causes of thyrotoxicosis, Graves' disease (GD) and Destructive thyroiditis (DT). Aims: The aim of this work was to study the role of FT3/FT4 ratio, T3/T4 ratio and color flow Doppler ultrasound in treatment-naïve patients with thyrotoxicosis, in comparison to Tc-99m pertechnetate thyroid scanning in the differentiation of thyrotoxicosis due to GD and DT. Materials and Methods: Clinical data was collected from all study subjects. Thyroid function tests including FT3, FT4, T3, T4 and TSH, TSH Receptor Antibody (TRAb), Technetium Tc 99m pertechnetate scan and the mean peak systolic velocity in inferior thyroid artery (mean PSV-ITA) by color Doppler ultrasonography of thyroid gland was done in all patients. Results: A total of 83 treatment-naïve patients with thyrotoxicosis (61 with GD and 22 with DT) were studied. Mean PSV-ITA, T3/T4 ratio and FT3/FT4 ratio showed a sensitivity of 85.2%, 73.8%, and 77.04%, and a specificity of 90.9%, 72.7%, and 59.09%, respectively. The three parameters in combination yielded a positive predictive value of 100% in the diagnosis of Graves' disease. Conclusion: Results of this study show that inferior thyroid artery blood flow, T3/T4 ratio and FT3/FT4 ratio are useful parameters in the differentiation between GD and DT.